Analisis Kestabilan Lereng Tunggal Menggunakan Metode Fellenius dan Slide v.6.0 serta Lereng Keseluruhan dengan GeoStudio 2012 pada Pit I Banko Barat PT Bukit Asam (Persero) Tbk Tanjung Enim – Sumatera Selatan - Devito Wirasto Simanjuntak; Ferra Fahraini; Anisa Indriawati (MINERAL, 2018)
Slopes are a topography that is often found in opened pit mine that had been made by humans with the purpose of exploiting minerals that exist. Landslides can occur on any slopes that is formed due to the increase of shear stress, shear strength declining in the field of landslides or both simultaneously. Slope stability analysis performed to obtain the value of the safety factor of the field of potential landslides. The study conducted at a coal mine Pit 1 Banko Barat PT Bukit Asam (Persero) Tbk by comparing the value of a single slope safety factor Fellenius with manual method to Slide v.6.0 software and the overall slope safety factor with software GeoStudio 2012 From the analysis performed on a single slope 1 to 9, safety factor values ​​obtained below 1.25 for single slopes 1 and single slope 2 to 9 above 1.25. Of the value of the safety factor is obtained, a single slope 1 in critical condition and the single slopes 2 to 9 in stable condition. While the overall slope stability analysis using GeoStudio 2012 program obtained average value of the safety factor - average is 4.57 so the slope can be declared in a stable condition. Then there are effforts to increase the safety factor (FK) of single slopes by changing a single slope geometry previously at an angle of 55 ° to 47 ° in order to obtain the condition of the slopes in a stable condition.